2017
DOI: 10.1038/srep46601
|View full text |Cite
|
Sign up to set email alerts
|

The pretreatment lymphocyte to monocyte ratio predicts clinical outcome for patients with hepatocellular carcinoma: A meta-analysis

Abstract: The lymphocyte-to-monocyte ratio (LMR) has been reported to predict clinical outcomes in multiple malignancies. The aim of this study was to assess the prognostic role of pretreatment LMR in hepatocellular carcinoma (HCC). A total of seven studies comprising 2,738 patients were included in the meta-analysis. Pooled results showed that elevated LMR was significantly associated with increased overall survival (OS) (HR: 0.31, 95% CI: 0.20–0.47, p < 0.001), disease-free survival (DFS)/recurrence-free survival (RFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 41 publications
3
34
2
Order By: Relevance
“…A meta‐analysis of HCC found that a high LMR is associated with increased overall survival and disease‐free survival after hepatic resection . The present study is the first to our knowledge to evaluate the significance of LMR in patients who underwent LT for HCC.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…A meta‐analysis of HCC found that a high LMR is associated with increased overall survival and disease‐free survival after hepatic resection . The present study is the first to our knowledge to evaluate the significance of LMR in patients who underwent LT for HCC.…”
Section: Discussionsupporting
confidence: 53%
“…A meta-analysis of HCC found that a high LMR is associated with increased overall survival and Original article | 1609 disease-free survival after hepatic resection. (22) The present study is the first to our knowledge to evaluate the significance of LMR in patients who underwent LT for HCC. Unlike hepatic resection for HCC, a healthy donor is required, and there are few effective therapies for the recurrence of HCC after LDLT.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, among patients with acute myocardial infarction, it has been shown that an increased NLR is a predictor of in-hospital mortality and morbidity [26], and impaired myocardial perfusion after percutaneous coronary angioplasty [27]. Similarly, LMR has been reported to be associated with adverse prognosis in multiple malignancies [22,28] and coronary artery disease [21,29].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils can contribute to chronic inflammation and promote tumor angiogenesis and growth by secreting specific molecules [46, 48]. A deficiency in or disruption of lymphocytes is involved in the SIR and promotion of malignancies [13, 47]. The NLR, calculated as the absolute neutrophil count divided by the absolute lymphocyte count, has often been investigated as a potential indicator in various tumors [49-51].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, SIR-related biomarkers, such as C-reactive protein (CRP) [12], the lymphocyte-monocyte ratio (LMR) [13], and the platelet-lymphocyte ratio (PLR) [14], have been investigated as potential predictors in bladder cancer. The neutrophil-lymphocyte ratio (NLR) has also been investigated as an economic and readily available predictor for bladder tumors in a few studies [15-19].…”
Section: Introductionmentioning
confidence: 99%